2022
DOI: 10.1186/s13643-022-02032-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cognitive remediation on activities of daily living in individuals with mild cognitive impairment or early-stage dementia: a systematic review and meta-analysis

Abstract: Introduction Instrumental activities of daily living are essential for ageing well and independent living. Little is known about the effectiveness of cognitive remediation on instrumental activities of daily living performance for individuals with mild cognitive impairment or early-stage dementia. The objective of this study was to evaluate the immediate and long-term carryover effects of cognitive remediation on improving or maintaining instrumental activities of daily living performance in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 73 publications
0
8
1
Order By: Relevance
“…The studies reported a statistically significant difference between groups in cognitive functions (attention, memory, executive function, languages, and global cognition) [ 77 , 78 , 79 , 80 , 82 ], in daily functioning [ 81 ], in depressive symptoms outcome [ 78 ], and in quality of life [ 77 ]. Compared with the previous systematic review and meta-analysis that used traditional CR methods and not fully immersive VR [ 87 , 88 ] our results suggested not only a cognitive functions improvement but also a general clinical improvement. The meta-analysis involved only people with MCI showed a positive effect on clinical cognitive outcomes specifically to memory, language, and global cognition.…”
Section: Discussioncontrasting
confidence: 61%
“…The studies reported a statistically significant difference between groups in cognitive functions (attention, memory, executive function, languages, and global cognition) [ 77 , 78 , 79 , 80 , 82 ], in daily functioning [ 81 ], in depressive symptoms outcome [ 78 ], and in quality of life [ 77 ]. Compared with the previous systematic review and meta-analysis that used traditional CR methods and not fully immersive VR [ 87 , 88 ] our results suggested not only a cognitive functions improvement but also a general clinical improvement. The meta-analysis involved only people with MCI showed a positive effect on clinical cognitive outcomes specifically to memory, language, and global cognition.…”
Section: Discussioncontrasting
confidence: 61%
“…A decrease in the ability to perform iADLs is linked to the initiation of cognitive decline, which can be a component of the natural aging process. The decline in iADL performance becomes increasingly noticeable as MCI emerges and becomes even more pronounced in cases of dementia [ 8 10 ]. As the world’s population ages, the incidence of dementia increases, a term that encompasses a variety of clinical diagnoses, including Alzheimer’s disease (AD), Parkinson’s disease, vascular dementia (VaD), frontotemporal dementia (FTD), Huntington’s disease and Lewy Body Dementia (LBD), each with their own causes and specific risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Effective early-intervention strategies for older adults with mild cognitive impairment to remediate and delay the deterioration of daily functioning are essential. A recent systematic review reported two types of cognitive interventions, including cognitive stimulation and cognitive training, that improve or remediate cognitive function [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive stimulation is used in activities that have been designed to increase cognition and social functioning in a non-specific manner, such as reading, playing chess, drawing and painting [ 7 , 8 ]. Cognitive stimulation activities target a specific cortical area that is related to the cognitive domain being investigated and boost cognitive reserves to prevent cognitive decline [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%